Integrasi Kitab Kuning dalam Kurikulum Pendidikan Agama Islam: Pendekatan Holistik di Ma'had Aly Imam Bukhari - Hanani, Hanif; Haerullah, Haerullah (TSAQOFAH, 2024)
This study aims to examine the importance of integrating the traditional Islamic texts known as kitab kuning into the Islamic education curriculum at Ma'had Aly Imam Bukhari. Kitab kuning, which covers fundamental Islamic sciences, is considered essential for providing students with a solid understanding of Islam. The research method used is a case study with a qualitative approach. Data were collected through interviews, participatory observation, and document analysis of the curriculum and teaching activities at Ma'had Aly Imam Bukhari. The findings indicate that kitab kuning forms the core of the educational curriculum at Ma'had Aly Imam Bukhari. Texts such as "Bidayatul Mujtahid" in the study of jurisprudence, "At-Tauhid" in the study of monotheism, "Qawa'idu Ushul wa Ma'aqidul Fushul" in the principles of Islamic jurisprudence, and "Al-Ilmam Bi Ba'dhi Ayatil Ahkam" in the exegesis of legal verses of the Quran are integral parts of the teaching. Additionally, "Bulughul Maram" in the study of hadith, "Qathrun Nada" in Arabic grammar, and "Tashilul Faraidh" in the study of Islamic inheritance law are also taught with comprehensive explanations from the instructors. In conclusion, the integration of kitab kuning into the Islamic education curriculum at Ma'had Aly Imam Bukhari has successfully strengthened the academic foundation and Islamic character of the students. The teaching of kitab kuning not only enhances the quality of Islamic education but also ensures that the authentic Islamic scholarly tradition remains preserved and relevant in the modern context. This study underscores the importance of kitab kuning as a primary source of Islamic knowledge and a crucial criterion for assessing the competence of an Islamic scholar or cleric.